The Use of Kampo Medicine for Acne: An Approach According to Five Exacerbating Factors - Nomoto, Mayumi (Archives of Clinical and Medical Case Reports, 2021)
Although the pathogenesis of acne has been elucidated, many patients do not notice improvement with standard treatments alone. Acne is a multifactorial disease, and although there are different aggravating factors such as diet, external stimuli, and stress that varies among individuals, the correct approach to tackling these factors has likely not been considered. Hence, we recommend using Kampo, a traditional Japanese medicine. Kampo examines a patient physically and mentally through unique concepts such as qi, blood, and fluid, and treats using Kampo medicines. With Kampo, both the illness and other aspects such as the general health and well being of the patient are examined and treated. We believe that if Kampo is employed in identifying and treating the aggravating factors of acne of each patient, both the overall therapeutic effect and patients’ motivation for treatment will be improved. This paper classifies the aggravating factors of acne into five categories, decreased barrier function of the skin, excessive secretion of sebum, exacerbation before menstruation, gastrointestinal symptoms, and stress, and introduces effective Kampo medicines in each case.